Optically Transparent Low Scattering Metasurface Based on Polarization Conversion‐Diffusion‐Absorption Integration Mechanism. Issue 4 (3rd February 2022) - Ran, Yuzhou; Shi, Lihua; Wu, Shuran; Fan, Bo; Jin, Xin; Ji, Dedong; Ma, Yao; Li, Jie; Liu, Yicheng; Wang, Jianbao
Abstract: In this paper, an optically transparent low‐scattering metasurface combining polarization conversion, diffusion, and absorption mechanisms is proposed. Firstly, a polarization conversion absorbing meta‐atom is designed, and its reflection coefficient is optimized based on equivalent circuit theory and genetic algorithm. Then, by arranging the meta‐atom and its orthogonal structural meta‐atom according to the random coding sequence, the metasurface is constructed, realizing the design concept of co‐polarization absorption and cross‐polarization diffusion. The simulation results are in good agreement with the measured results and the Radar Cross Section (RCS) reduction of more than −10 and −25 dB can be realized in the co‐polarized and cross‐polarized directions in 3.3–12.3 GHz, respectively. Moreover, the amplitude and bandwidth of RCS reduction of the metasurface can be maintained well in the 0–40° oblique incidence range. Abstract : An optically transparent low‐scattering metasurface combining polarization conversion, diffusion, and absorption mechanisms is proposed. The reflection coefficient of absorbing meta‐atom is optimized based on equivalent circuit theory and genetic algorithm. Radar Cross Section reduction of more than −10 and −25 dB can be realized in the co‐polarized and cross‐polarized directions in 3.3–12.3 GHz.